Pan-cancer analysis of the prognosis and immune infiltration of NSUN7 and its potential function in renal clear cell carcinoma - Jinwei Cui; Shiye Ruan; Zhongyan Zhang; Hailiang Wang; Qian Yan; Yubin Chen; Jiayu Yang; Jike Fang; Qianlong Wu; Sheng Chen; Shanzhou Huang; Chuanzhao Zhang; et al. (Discover Oncology)
Abstract Background NSUN7, an enzyme responsible for the RNA m5c modification, has been recognized as a valuable indicator for predicting and diagnosing an array of cancer. Nevertheless, there is still a scarcity of thorough analyses exploring its diagnostic, predictive, and immune system-related importance in various types of cancer. Methods We integrated multiple publicly available databases, including TCGA, TISIDB, TISCH2, and UALCAN, to comprehensively investigate the role of NSUN7 in pan-cancer across various omics data types. The research included examining survival rates, genetic mutations, immune cell presence in tumors, analyzing differences in gene expression, and studying individual cells, among other things. Results NSUN7 expression showed an increase across 12 cancer types and a decrease in another 12 types. NSUN7 was discovered to be linked with enhanced survival rates in bladder urothelial carcinoma (BLCA), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), lung adenocarcinoma (LUAD), pheochromocytoma and paraganglioma (PCPG), skin cutaneous melanoma (SKCM), and uveal melanoma (UVM).On the other hand, NSUN7 seemed to have a detrimental impact on the prognosis of glioblastoma multiforme/brain lower grade glioma (GBMLGG), adrenocortical carcinoma (ACC),acute myeloid leukemia (LAML), stomach adenocarcinoma (STAD), and brain lower grade glioma (LGG). Furthermore, our experimental validation confirmed the inhibitory effect of NSUN7 on proliferation of renal clear cell carcinoma while elucidating its specific part in blocking cell cycle progression. Conclusions The findings underscore the potential utility of NSUN7 as a valuable prognostic indicator for patients and offer insights into the mechanisms underlying cancer initiation and progression.